Does subclinical inflammation contribute to impairment of function of knee joints in aged individuals? High prevalence of ultrasound inflammatory findings - D'Agostino, Maria Antonietta; Iagnocco, Annamaria; Aegerter, Philippe; Kleyer, Arnd; Zwerina, Jochen; Perricone, Carlo; Lorenzini, Rolando; Aschenbrenner, Franz; Willeit, Johann; Kiechl, Stefan; Schett, Georg (Rheumatology, 2015)
To investigate the prevalence of knee US findings of inflammation and structural damage in aged individuals (>=60 years) of a long-term population-based cohort and to correlate these findings with demographic, clinical and laboratory parameters.Cross-sectional clinical and US investigation of both knee joints during the 2010 follow-up of the prospective population-based Bruneck Study. Demographic variables, physical activity, comorbidities, medications, pain, and functional scales related to the knee joints were recorded. US-assessed parameters were synovial hypertrophy, power Doppler signal, joint effusion, cartilage abnormalities, osteophytes, enthesopathy and bursitis. Statistics included univariate and multivariate regression analysis.A total of 488 subjects (mean age 72.5 years; 53.5% females, 46.5% males) were examined by clinical assessment, and 433 of these underwent US examination of both knees. Both inflammatory and structural abnormalities were found in 296 (68.8%) subjects. Inflammatory abnormalities were significantly associated with age in years, male gender, diabetes and the presence of knee joint symptoms. In the multivariate analysis, age, male gender and knee swelling emerged as independent predictors of inflammation [odds ratio (OR) (95% CI) = 1.06 (1.03, 1.09), 2.55 (1.55, 4.21) and 5.92 (1.99, 17.58), respectively].The present study showed a high prevalence of US inflammatory abnormalities in the knee joints of a normal aged population. These data suggest a substantial contribution of inflammation in progressive impairment of joint function with age.
EVALuna2:13126